Les lecteurs de Samokov au XIXe siècle - Stoyanka Kenderova (Revue des Mondes Musulmans et de la Méditerranée)
The Samokov library founded in 1840 by the governor Mehmed Hüsrev Paşa (D. 1847) was one of the richest 19th century vakiflibraries in Bulgaria. In 1888, when die Sofia library took it over, there were 2,485 volumes in the Arab, Tukish and Persian. The reading log of the library's first year of operation figured among the volumes. Its study allows one to have an idea of the classification used at that time (there were 26 types of classification), the number of readers, their names, social origins and their choice of reading.